2021
DOI: 10.3389/fcvm.2021.646832
|View full text |Cite
|
Sign up to set email alerts
|

circ_0003204 Regulates Cell Growth, Oxidative Stress, and Inflammation in ox-LDL-Induced Vascular Endothelial Cells via Regulating miR-942-5p/HDAC9 Axis

Abstract: Background: Atherosclerosis (AS) is a typical inflammatory vascular disease. Many reports corroborated that circular RNAs (circRNAs) is involved in AS progression. However, the potential function and possible mechanism of circ_0003204 in AS progression remain indistinct.Methods: Expression level analysis was performed using qRT-PCR and western blot. Cell viability and apoptosis were determined using Cell Counting Kit-8 (CCK-8), flow cytometry, and western blot assays. The status of oxidative stress and inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Moreover, previous studies reported that circ_0003214 attenuated the capacities of proliferation, migration and angiogenesis in ox-LDL-administered human aorta endothelial cells (HAECs) and HUVECs [22,23]. In addition, circ_0003204 silencing was also demonstrated to suppress oxidative stress and inflammatory responses in ox-LDL-treated HUVECs [24]. Consistent with these findings, our data manifested that circ_0003204 deficiency alleviated ox-LDL-induced inflammation, cell viability inhibition, cell apoptosis and tube formation inhibition of HUVECs.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, previous studies reported that circ_0003214 attenuated the capacities of proliferation, migration and angiogenesis in ox-LDL-administered human aorta endothelial cells (HAECs) and HUVECs [22,23]. In addition, circ_0003204 silencing was also demonstrated to suppress oxidative stress and inflammatory responses in ox-LDL-treated HUVECs [24]. Consistent with these findings, our data manifested that circ_0003204 deficiency alleviated ox-LDL-induced inflammation, cell viability inhibition, cell apoptosis and tube formation inhibition of HUVECs.…”
Section: Discussionsupporting
confidence: 90%
“…According to previous studies, miR-942-5p could attenuate oxidative stress and inflammation in an in vivo atherosclerosis model. 38 IgG Fcγ receptors are encoded by FCGR3A and FCGR3B, which in turn mediate immune cell activation promoting inflammation. 39 Regrettably, there is no evidence in the literature that the RNA molecules described above may be involved in the neuroinflammation of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that TTTY15 may be involved in the pathogenesis of diabetic nephropathy by targeting and regulating the expression of miR-942-5p. miR-942-5p has been shown to be poorly expressed in oxidative-Low Density Lipoprotein (ox-LDL) induced endothelial cell injury and up-regulation of miR-942-5p expression reduces ox-LDL-induced endothelial cell injury [16] . miR-942-5p is poorly expressed in adriamycin-induced cardiomyocytes and up-regulation of miR-942-5p expression inhibits doxorubicin-induced cardiomyocyte apoptosis [17] .…”
Section: Resultsmentioning
confidence: 99%